Archaeometric Study of Volcanic Lithic Objects from The Longola (Poggiomarino) Protohistoric Site, Southern Italy: Regional Versus Extra‐Regional Provenance. (28th July 2015) - Balassone, G.; Santi, P.; Renzulli, A.; Di Maio, G.; Mondillo, N.; Monetti, V.
Abstract : The Longola protohistoric village (spanning from the late Middle Bronze Age to the sixth centurybc ) is a perifluvial settlement located in the Sarno River floodplain to the north‐east of Pompeii (southern Italy) and east of the Somma‐Vesuvius volcano. A great abundance of artefacts have been found at Longola and in the neighbouring areas, including a variety of volcanic stone objects, mainly related to building and to the manufacture of ordinary tools and instruments. The aim of our work is to characterize lithic objects (lava pebbles and millstones) and to understand their geological provenance by petrographic and geochemical studies. Compositions of millstone samples (porphyritic phonolitic tephrites) and of a set of pebbles (mainly phonolitic tephrites, leucite–shoshonites and trachytes) are compatible with the Somma‐Vesuvius magmas erupted before 8 ka bp . For the trachyte lithics, an additional source from the Accademia lava dome (Phlegrean Fields) cannot be ruled out. Among the pebble samples, a rhyolite and a poorly evolved trachyte clearly lie outside the compositional variation of the Somma‐Vesuvius and other volcanoes of the Naples area (e.g., Ischia and the Phlegrean Fields) and emphasize an extra‐regional provenance. Ponza Island is the best candidate for the provenance of the above two outlier samples.